W. F. Nietzsche's Philosophical thoughts in the Roman also Sprach Zarathustra and Its Dimensions of Religiosity - Reza, Muhammad; Muslima, Alfia Tawaffani; Syihabuddin, Syihabuddin (Budapest International Research and Critics University, 2022)
This study discusses Nietzsche's philosophical thoughts in the roman entitled Also Sprach Zarathustra based on its hypogrammatic relationship with the dimensions of religiosity. The method used is qualitative. The results of this study indicate that literature and philosophy can have a relationship. From the research conducted, the matrix in roman is Superior Man (Ãœbermensch) and Will to Power (das Will zur Macht) as the philosophical thoughts of him. Meanwhile, the dimensions of religiosity in the roman can be seen from two dimensions, namely 1). the ideological dimension (Religious Belief) in the form of belief in the existence of dogmatic things (spirit, God, angels, heaven, hell) which is metaphorized as a spirit that always gives as heiligen Ja-sagen. The holy Yes attitude (heiligen Ja-sagen) is an affirmation of life that is concretely manifested in the recognition of all kinds of impulses (both scary and enchanting) that people personify as God. 2). Dimensions of Consequences (Religious Effect) are dimensions that measure the extent to which a person's behavior is motivated by his religious nature. The new moral value created by Nietzsche is to reject the moral system with rules and punishments. The new value created by Nietzsche is with the freedom of will to rule, regulate himself and not show sanctions as the reason, he shows more on the process of individual consciousness to accept the truth of morality without conditions.